Racismo, este estranho familiar - Conte, Bárbara de Souza; Schwarcz, Lilia Moritz; Silva, Maria Lúcia da; Kon, Noemi Moritz (Percurso, 2015)
Realização: Cristiane Abud Curi, Gisela Haddad, Thiago Majolo e Vera Zimmermann